4(x-4)=-2(x+1)

Simple and best practice solution for 4(x-4)=-2(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-4)=-2(x+1) equation:


Simplifying
4(x + -4) = -2(x + 1)

Reorder the terms:
4(-4 + x) = -2(x + 1)
(-4 * 4 + x * 4) = -2(x + 1)
(-16 + 4x) = -2(x + 1)

Reorder the terms:
-16 + 4x = -2(1 + x)
-16 + 4x = (1 * -2 + x * -2)
-16 + 4x = (-2 + -2x)

Solving
-16 + 4x = -2 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-16 + 4x + 2x = -2 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-16 + 6x = -2 + -2x + 2x

Combine like terms: -2x + 2x = 0
-16 + 6x = -2 + 0
-16 + 6x = -2

Add '16' to each side of the equation.
-16 + 16 + 6x = -2 + 16

Combine like terms: -16 + 16 = 0
0 + 6x = -2 + 16
6x = -2 + 16

Combine like terms: -2 + 16 = 14
6x = 14

Divide each side by '6'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| 4(x+3)-6=15-4x-9+8x | | 2x+n=210 | | -7+(-3)x+5+(-6)x= | | 0.18(y-8)+0.08y=0.06y-0.09(30) | | 6w-2w=44 | | 5(x+4)=3x-2(4) | | 5x^2-40+75=0 | | 0.50x+0.45(70)=0.25(114) | | -6(x-2)=3(x+14) | | 5/12+a=11/12 | | 20+n=1 | | 40t+55x= | | 1.5+0.3r=-4.2 | | 4-5k=-4k+7 | | 15y-3x=-6 | | a=400+(-80)(1-1) | | x+12=17-4x | | 160+0.25n=342.50 | | 6(3x-2)=3x+5x | | 10x-25=625 | | x/10-5/2+x=3x/5 | | 3n+1=5n+8 | | 4(m+3)=44 | | 2x+4259=210355 | | 2(x-8)=10 | | 9x+6y=18 | | -2y=4-6x | | 2(3x-1)=4x+5 | | 5(x+5)=64 | | 3(2f-6)+6=36 | | 3n+2(4n-5)-7+n= | | -6x+2x=3x |

Equations solver categories